2015
DOI: 10.1093/mnrasl/slv027
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties of polycrystalline dense matter

Abstract: Elastic properties of the solid regions of neutron star crusts and white dwarfs play an important role in theories of stellar oscillations. Matter in compact stars is presumably polycrystalline and, since the elastic properties of single crystals of such matter are very anisotropic, it is necessary to relate elastic properties of the polycrystal to those of a single crystal. We calculate the effective shear modulus of polycrystalline matter with randomly oriented crystallites using a self-consistent theory tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 22 publications
(23 reference statements)
0
40
0
Order By: Relevance
“…For strain |ǫ| 0.04 the stress-strain curve for the polycrystalline MD simulation inFig. 1ofHorowitz & Kadau (2009) agrees well with the results ofOgata & Ichimaru (1990), but not with those ofKobyakov & Pethick (2015). However, this can be a specific property of this particular polycrystal.…”
mentioning
confidence: 50%
“…For strain |ǫ| 0.04 the stress-strain curve for the polycrystalline MD simulation inFig. 1ofHorowitz & Kadau (2009) agrees well with the results ofOgata & Ichimaru (1990), but not with those ofKobyakov & Pethick (2015). However, this can be a specific property of this particular polycrystal.…”
mentioning
confidence: 50%
“…In any case, it is obvious from Fig. 5 that the location of the stars, inside or outside the instability window, depends strongly on the value of the factor S. In view of the above discussion, it is concluded that the study of the elastic properties of the crust is a very important issue in neutron star physics (for a recent study see [33]). To clarify further this statement, we display in Fig.…”
Section: /4mentioning
confidence: 87%
“…Recently, this shear modulus has been modified by taking into account the effect of electron screening (Kobyakov & Pethick 2013) and the effect of polycrystalline nature (Kobyakov & Pethick 2015). In this study, however, we adopt the traditional formula given by Eq.…”
Section: Shear Modulusmentioning
confidence: 99%